It takes a village to educate a child: LLV’s evolving story of building innovation in a context of constraint - Fiona Young; Meredith Ash; Stephanie McConnell (IUL Research)
Lindfield Learning Village in Sydney, Australia, is an innovative K-12 public school challenging traditional educational approaches and demonstrating excellence in practice and outcomes. Its unique educational model, based on stage-not-age, student-centred and authentic real-world transdisciplinary learning has attracted widespread interest with waitlists of up to 2500 students. Characterised by its innovative learning environments and diverse suite of shared spaces, the school is configured as a cross-stage hub model to optimise opportunities for all students and staff to develop meaningful relationships in smaller cohorts as-well-as enable stage-based learning. Since opening in 2019, the school has continually piloted and evolved its pedagogical practices and learning spaces. This paper discusses the process of creating the school’s vision and educational model, and key steps in implementing a process of pedagogical transformation to enable the school as it is today.